Design, synthesis, and evaluation of the novel ozagrel–paeonol codrug with antiplatelet aggregation activities as a potent anti-stroke therapeutic agent - Zuo, Chijing; Yan, Fulong; Wang, Jie; Zhu, Yulong; Luo, Wenhui; Liu, Yan; Liang, Wanhui; Yu, Weidong; Zhang, Jingwei; Peng, Daiyin; Ma, Xiaodong; Peng, Can (Frontiers in Pharmacology, 2024)
Introduction: Ischemic stroke is the second most common chronic disease worldwide and is associated with high morbidity and mortality. Thromboembolism and platelet aggregation are the most characteristic features of stroke. Other than aspirin, no standard, accepted, or effective treatment for acute ischemic stroke has been established. Consequently, it is essential to identify novel therapeutic compounds for this condition. Methods: In this study, novel ozagrel/paeonol-containing codrugs were synthesized and characterized using 1H-NMR, 13C-NMR, and mass spectroscopy. Their antiplatelet aggregation activity was evaluated, with compound PNC3 found to exhibit the best effect. Subsequently, studies were conducted to assess its neuroprotective effect, pharmacokinetic properties and model its binding mode to P2Y12 and TXA2, two proteins critical for platelet aggregation. Results: The results indicated that PNC3 has good bioavailability and exerts protective effects against oxygen-glucose deprivation injury in PC12 cells. Molecular docking analysis further demonstrated that the compound interacts with residues located in the active binding sites of the target proteins. Conclusion: The codrugs synthesized in this study display promising pharmacological activities and have the potential for development as an oral formulation.